Brain structural differences in children with fetal alcohol spectrum disorder and its subtypes - Boateng, Theresah; Beauchamp, Kathryn; Torres, Faerl; Ruffaner-Hanson, Chaselyn D.; Pinner, John F. L.; Vakamudi, Kishore; Cerros, Cassandra; Hill, Dina E.; Stephen, Julia M. (Frontiers in Neuroscience, 2023)
The teratogenic effects of prenatal alcohol exposure (PAE) have been examined in animal models and humans. The current study extends the prior literature by quantifying differences in brain structure for individuals with a fetal alcohol spectrum disorder (FASD) compared to typically developing controls, as well as examining FASD subtypes. We hypothesized the FASD group would reveal smaller brain volume, reduced cortical thickness, and reduced surface area compared to controls, with the partial fetal alcohol syndrome (pFAS)/fetal alcohol syndrome (FAS) subtypes showing the largest effects and the PAE/alcohol-related neurodevelopmental disorder (ARND) subtype revealing intermediate effects. The sample consisted of 123 children and adolescents recruited from a single site including children with a diagnosis of FASD (26 males, 29 females) and controls (34 males , 34 females). Structural T1-weighted MRI scans were obtained on a 3T Trio TIM scanner and FreeSurfer v7.2 was used to quantify brain volume, cortical thickness, and surface area. Analyses examined effects by subgroup: pFAS/FAS (N=32, M age =10.7 years, SE age = 0.79), PAE/ARND (N=23, M age =10.8, SE age 0.94), and controls (N=68, M age =11.1, SE age = 0.This is a provisional file, not the final typeset article controls, but subtype analysis revealed only the pFAS/FAS group differed significantly from controls. Regional analyses similarly revealed reduced brain volume in frontal and temporal regions for children with pFAS/FAS, yet children diagnosed with PAE/ARND generally had similar volumes as controls. Notable differences to this pattern occurred in the cerebellum, caudate, and pallidum where children with pFAS/FAS and PAE/ARND revealed lower volume relative to controls. In the subset of participants who had neuropsychological testing, correlations between volume and IQ scores were observed. Goodness-of-Fit analysis by age revealed differences in developmental patterns (linear vs. quadratic) between groups in some cases. This study confirmed prior results indicating decreased brain volume in children with an FASD and extended the results by demonstrating differential effects by structure for FASD subtypes. It provides further evidence for a complex role of PAE in structural brain development that is likely related to the cognitive and behavioral effects experienced by children with an FASD.